Development of Neuron Ion Channel Model using Colored Noise Terms in the Conductance - Khudhur, Ahmed M.; Hashim, Yasir; Abdalla, Ahmed N. (Maxwell Scientific Publication Corp., 2017)
The aim of this study is the ion channel model with noise variance as approximations to the HodgkinHuxley model proposed, due to the Hodgkin-Huxley model affected when inserting some colored noise terms inside the conductances, where those effects captured by colored noise because of the gate multiplicity. Firstly, it introduces the comparison of ion channel based on Fox, Lu and Linaro models. Additionally, in order to overcome the limitations of other parameter estimation methods, the proposed method fully constrains their models and obtains all model's capabilities of reproducing the data. Finally, the relationship between the sequence of colored noise and the spike frequency are simulated efficiently each gate compared with microscopic simulations of the stochastic Markov process method. In simulation results, the spiking rate generated from the proposed model very close to microscopic simulations and doesn’t effect by the membrane size.